Jahresbericht 2005 : Die Vorteile der Weltwirtschaft fur alle sichern. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2005)
The Annual Report 2005 to the Board of Governors reviews the IMF's activities and policies during the financial year (May 1, 2004, through April 30, 2005). The main sections cover country, global, and regional surveillance; strengthening surveillance and crisis prevention; IMF program support and crisis resolution; the Fund's role in low-income countries; financial operations and policies; technical assistance and training; governance and management of the IMF; and cooperation, communication and outreach. Besides the full financial statements for the year, appendixes cover international reserves, financial operations and transactions, principal policy decisions, relations with other international organizations, press communiques of advisory committees, Executive Directors and their voting power, and changes in the Executive Board's membership.